A Legacy of Animosity in the Southern Cone of South America? Attitudes of Paraguayan Consumers Towards Argentina and Brazil - Michael Pisani; Alcides G. Cáceres Zarate; José-Carlos Tello; Silvio Eduardo Becker (RAN, 2024)
Purpose: This article explores the interconnection between Paraguayan consumer behavior and products from Argentina and Brazil, situating the study within the context of past hostilities (animosity) and present uneven relations among the three nations.